A graduate student perspective on overcoming barriers to interacting with open-source software - Oihane Cereceda; Danielle E.A. Quinn (Canadian Science Publishing, 2020)
Computational methods, coding, and software are important tools for conducting research. In both academic and industry data analytics, open-source software (OSS) has gained massive popularity. Collaborative source code allows students to interact with researchers, code developers, and users from a variety of disciplines. Based on the authors' experiences as graduate students and coding instructors, this paper provides a unique overview of the obstacles that graduate students face in obtaining the knowledge and skills required to complete their research and in transitioning from an OSS user to a contributor: psychological, practical, and cultural barriers and challenges specific to graduate students including cognitive load in graduate school, the importance of a knowledgeable mentor, seeking help from both the online and local communities, and the ongoing campaign to recognize software as research output in career and degree progression. Specific and practical steps are recommended to provide a foundation for graduate students, supervisors, administrators, and members of the OSS community to help overcome these obstacles. In conclusion, the objective of these recommendations is to describe a possible framework that individuals from across the scientific community can adapt to their needs and facilitate a sustainable feedback loop between graduate students and OSS.